If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 1)(x + -1) = 64 Reorder the terms: (1 + X)(x + -1) = 64 Reorder the terms: (1 + X)(-1 + x) = 64 Multiply (1 + X) * (-1 + x) (1(-1 + x) + X(-1 + x)) = 64 ((-1 * 1 + x * 1) + X(-1 + x)) = 64 ((-1 + 1x) + X(-1 + x)) = 64 (-1 + 1x + (-1 * X + x * X)) = 64 (-1 + 1x + (-1X + xX)) = 64 Reorder the terms: (-1 + -1X + 1x + xX) = 64 (-1 + -1X + 1x + xX) = 64 Solving -1 + -1X + 1x + xX = 64 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -1X + 1x + 1 + xX = 64 + 1 Reorder the terms: -1 + 1 + -1X + 1x + xX = 64 + 1 Combine like terms: -1 + 1 = 0 0 + -1X + 1x + xX = 64 + 1 -1X + 1x + xX = 64 + 1 Combine like terms: 64 + 1 = 65 -1X + 1x + xX = 65 Add '-1x' to each side of the equation. -1X + 1x + -1x + xX = 65 + -1x Combine like terms: 1x + -1x = 0 -1X + 0 + xX = 65 + -1x -1X + xX = 65 + -1x Reorder the terms: -65 + -1X + x + xX = 65 + -1x + -65 + x Reorder the terms: -65 + -1X + x + xX = 65 + -65 + -1x + x Combine like terms: 65 + -65 = 0 -65 + -1X + x + xX = 0 + -1x + x -65 + -1X + x + xX = -1x + x Combine like terms: -1x + x = 0 -65 + -1X + x + xX = 0 The solution to this equation could not be determined.
| 3+2(5x-1)=2x+3(4-5x) | | 4x^2=-5x+21 | | x+7-3=12 | | 17(x-2)-1=15x+3 | | 5-9+2= | | x+85=165 | | 3v^2-3=-8v | | 200+3=27+170+x | | 1-2/x/x-4/x | | 27x+5=32 | | 8d+d=63 | | 5x+8y=-24 | | f(x)=3x^2-24x-130 | | f(x)=3x^2-24x-30 | | 189-y=39 | | 89x-5=-1152 | | 3y-5=18+8y | | 8p^2=-64p | | 12.48= | | 18x^2-29x=0 | | 34x=102 | | (X+10)(x+5)=0 | | (4x^2+1)+(19x+4)+(x^2+7x)= | | 2y=8m-3 | | -2+7=1x | | 1/3x=48 | | 1/3x=38 | | x-3=4+5 | | 35z^3y^5-16zy^5/-4z^2y^4 | | U=5(4n+30)+9(n+1) | | 20X=144-12X | | 4z+5z+2=148 |